Low Prevalence of Thrombosis Prophylaxis Dose Adjustments Highlights Implications for Patient Safety - W. Anthony Hawkins (University of Minnesota Libraries Publishing, 2021)
Background: Pharmacologic thromboprophylaxis (PTP) is the mainstay prevention strategy for venous thromboembolism (VTE). PTP agents traditionally dosed, like unfractionated heparin (UFH) and enoxaparin (ENOX), are associated with failure and bleeding in obese and underweight patients, respectively.